Efektivitas pendidikan kewirausahaan dan penggunaan media sosial terhadap minat berwirausaha mahasiswa - Joy Angelica Tjahjono; Maya Malinda (Universitas Kristen Maranatha, 2026)
In the rapidly developing digital era, entrepreneurship education focuses not only on developing technical skills, but also on strengthening critical, innovative, and collaborative thinking abilities. Social media has become an essential tool in the modern business world, playing a vital role in market research, product marketing, and professional network development. Therefore, the integration of social media in entrepreneurship learning is very important to equip students with relevant skills in an increasingly competitive business world. This research aims to examine the relationship between the influence of entrepreneurship education and social media on the entrepreneurial interest of students in the Bachelor of Management Department at Maranatha Christian University. This research uses an associative quantitative approach, which aims to determine the relationship between variables. Research findings show that social media and entrepreneurship education both significantly influence interest in entrepreneurship at the same time. This research confirms that entrepreneurship education and the use of social media play a significant role in building students' interest in entrepreneurship through increasing knowledge, skills, and exploiting opportunities, and is expected to become a better learning standard for academics and universities.